Persatoean Arab Indonesia (PAI): Arab-Hadrami Community Integration Movement in the Dutch East Indies, 1934-1942 - Taslim Batubara; Ahmad Muhajir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2022)
This article aims to explain how the involvement and success of the Persatoean Arab Indonesia (PAI) in integrating Arab-Hadrami society into a part of the Indonesian nation. PAI was originally a social organization founded in Semarang in 1934. But along the way, this organization turned into a political organization because of the demands of its time. This article uses historical research methods in four steps, i.e., heuristics, verification, interpretation, and historiography. The main source in this article is the personal archive of A. R. Baswedan, organizational archives of Persatoean Arab Indonesia (PAI), and Koempoelan Toelisan Gerakan al-Irsjad. While the supporting sources come from contemporaneous newspapers, e.g., Pewarta Arab, Insaf, Matahari, Al-Ma’arif, ad-Dahna, Hadhramaut dan Aliran Baroe, as well as secondary sources derived from books, journals, and other scientific articles relevant to this topic. The results showed that: (1) Persatoean Arab Indonesia (PAI) was founded as a solution to reconcile the opposition among sayidi and non-sayid groups that divided the Arab-Hadrami community in the Dutch East Indies. Along the way, PAI then gained the support of the two conflicting groups; (2) PAI succeeded in integrating the Arab-Hadrami community into part of the Indonesian nation. Although at first the Indonesianized of this organization was doubtful, with its various programs, PAI managed to attract sympathy from nationalists and the Indonesian people that they were part of this nation.